Medication Errors Associated with Beta-Lactam Antibiotics: Analysis of Russian Spontaneous Reporting Database - A. V. Kuzmina; I. L. Asetskaya; V. A. Polivanov; S. K. Zyryanov (Антибиотики и Химиотерапия)
The authors conducted a retrospective analysis of Russian database of spontaneous reports (SRs) for the period from 01.01.2012 to 01.08.2014. They analyzed 3608 SRs concerning adverse drug reactions associated with beta-lactam antibiotics to identify medication errors (MEs). MEs were detected in 1043 (28.9%) SRs, total amount of MEs was 1214. Medication error-related terms were indicated by reporters in 29 (0.8%) SRs. The most common types of identified MEs were inappropriate indication for the antibiotic - 32.5% MEs, deviations from the recommended dosing scheme - 29.7% MEs, and the use of contraindicated drug - 17.3% MEs. The use of antibiotics for viral infections and errors associated with a patient with documented hypersensitivity to administered drug pose a special problem. The highest number of SRs with MEs was associated with the use of cefazolin (50.8% SRs), amoxicillin (40.9% SRs), amoxicillin/clavulanate (40.0% SRs). The study shows the need to develop measures for prevention of MEs associated with the use of beta-lactam antibiotics in clinical practice.